Differential diagnosis in neuroendocrine neoplasms of the Larynx - Hunt, Jennifer L. (2019)
The differential diagnosis of neuroendocrine neoplasms of the larynx is broad and includes lesions of epithelial, mesenchymal, and neuroectodermal origin. These lesions have overlapping clinical and pathologic aspects and must be carefully considered in the differential diagnosis of laryngeal neoplasms. The prognosis and treatment are also different among these tumor types, which necessitates making these distinctions clinically. The current literature was reviewed to provide updated information regarding the epithelial-derived tumors, including carcinoid, atypical carcinoid, small cell neuroendocrine carcinomas, large cell neuroendocrine carcinoma, and squamous cell carcinoma with neuroendocrine component. These tumors are compared and contrasted with nonepithelial-derived tumors such as paraganglioma and nonmucosal tumors, such as medullary thyroid carcinoma. The morphologic and cytologic features are discussed, along with helpful immunohistochemical and ancillary investigations.